2022
DOI: 10.1101/2022.10.18.512627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Annotating and prioritizing human non-coding variants with RegulomeDB

Abstract: Nearly 90% of the disease risk-associated variants identified from genome-wide association studies (GWAS) are in non-coding regions of the genome. The annotations obtained from analyzing functional genomics assays can provide additional information to pinpoint causal variants, which are often not the lead variants identified from association studies. However, the lack of available annotation tools limits the use of such data. To address the challenge, we have previously built the RegulomeDB database for priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The continuously growing corpus of genomic data captures an increasingly complete view of human regulatory variation. RegulomeDB recently upgraded to version 2, expanding to >650 million and >1.5 billion genomic intervals in hg19 and GRCh38, respectively (11). The large discrepancy in the data availability between the two assemblies, for example in ChIP-seq and open chromatin data (RegulomeDB TF ChIP-seq availability in Fig 1a, open chromatin in Supplementary Fig 3, histone ChIP-seq in Supplementary Fig 4), results from better representation of complex variation and correction of sequencing artifacts in the GRCh38 assembly (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuously growing corpus of genomic data captures an increasingly complete view of human regulatory variation. RegulomeDB recently upgraded to version 2, expanding to >650 million and >1.5 billion genomic intervals in hg19 and GRCh38, respectively (11). The large discrepancy in the data availability between the two assemblies, for example in ChIP-seq and open chromatin data (RegulomeDB TF ChIP-seq availability in Fig 1a, open chromatin in Supplementary Fig 3, histone ChIP-seq in Supplementary Fig 4), results from better representation of complex variation and correction of sequencing artifacts in the GRCh38 assembly (12).…”
Section: Resultsmentioning
confidence: 99%
“…RegulomeDB intersects query variants with regulatory regions predicted by functional genomics assays and, by utilizing ranking heuristics, informs users about putative functional consequences to prioritize variants. Recently, RegulomeDB has been upgraded to version 2 (11), improving its annotation power by incorporating thousands of new functional genomics datasets from the ENCODE project (12), Roadmap Epigenomics Consortium (13), and the Genomics of Gene Regulation Consortium. A suite of models, namely SURF and TURF, was developed and integrated in this version to provide accurate probabilistic scores for general and cell-type specific regulatory activities (14, 15).…”
Section: Introductionmentioning
confidence: 99%
“…As most variants associated with complex traits are in the non-coding genome, discovering functional variants is constrained by methodological limitations. Computational approaches have been developed that utilise variable genomic features to aid variant prioritisation , including variable use of functional annotations, conservation scores, and TF motifs (Wang et al, 2022, Dong et al, 2023. However, for non-coding variants these methods tend to have low precision for identifying functional variants (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Using the RegulomeDB v2.2 44 , we found that most elements have predicted regulatory function, either assuming multiple functions, or as enhancers only or repressors only. About one third of the elements are predicted to be quiescent or transcribed (Figure 5D).…”
Section: Genome-wide Analysis Of Gwas Significant Variants Uncovers T...mentioning
confidence: 99%
“…We downloaded multiple alignment sequence files across eight species (including zebrafish, medaka, stickleback, tetraodon, fugu, frog, mouse, and human) from the UCSC Genome Browser and analyzed the alignments with Biopython to discover conserved elements that contain our GWAS significant SNP variants. Regulatory function of the elements conserved between zebrafish and human were further explored using RegulomeDB 44 .…”
Section: Discovery and Bioinformatics Analysis Of Gwas Significant Va...mentioning
confidence: 99%